Educação e gestão da segurança contra incêndio: estudo de caso dos ambientes audiovisuais de uma instituição federal de ensino - Santos, Marco Aurélio Araujo dos (2018)
Every year, fires in public educational institutions and other public properties cause a substantial number of civilian deaths and injuries and significant property damage in the Brazil. This research is about Education and Fire Safety Management, linking it to the culture and occupational health and safety in an educational institution. This is a case study research in Fire Safety Awareness of audiovisual installations at federal educational institution. Fire Safety Management failures in public schools or colleges & universities to focus on prevention and control methods of fire suppression interfere with the efficient fire suppression, for educational institutions where there might be limited resources or high risk in case of fire to extinguish or prevent the spread of fire. The aim of this research is to promote the Fire Safety Awareness, Safety Culture, to identify future safety failures leads to improved planning, and raising environmental awareness and providing information through education to employees and students. The following culture types were then analyzed: school culture, organizational culture and safety culture. Implications of these three theoretical perspectives for the ways sociologists think about the theoretical contributions of Critical Theory in the research was Adorno and Horkheimer’s concepts of culture and awareness, discussing the barriers to awareness and education. Finally, the research propose recommendations to improve the Fire Safety Management at federal educational institution.